Avaliação dos efeitos ecotoxicológicos de pesticidas : aplicação de bioensaios e estratégia de mitigação - Cotrim, Carlos Filipe Camilo (2024)
Pesticides are essential for protecting crops against pests; however, they have effects on humanhealth and the environment. Understanding the effects associated with the use of thesemolecules and establishing strategies for their degradation in the environment is of utmostimportance. Therefore, the present thesis aims to evaluate the toxic, cytogenotoxic, mutagenic,and environmental effects of pesticides. To this end, bioassays and soil parameter analyses wereused to identify the effects associated with the evaluated compounds and explore the fungalpotential for mycodegradation processes of the active ingredients. Initially, a literature reviewwas conducted on the use of Allium cepa as a bioassay to assess the cytogenotoxic andmutagenic potential of pesticides. It was found that the A. cepa bioassay is effective andappropriate for evaluating pesticide toxicity. The analyzed studies collectively investigated 113pesticides that caused some level of toxicity, mainly interference with the mitotic spindle. Thebioassay of A. cepa root exposure to four concentrations of the pesticide fluopyram (Verango®Prime) (5.00 (3×), 1.67 (field), 0.835 (50%), and 0.17 (10%) mg mL-1) demonstrated that it didnot cause lipid peroxidation but induced cytotoxic and genotoxic effects, varying according toconcentrations and phases of exposure or recovery. To evaluate the mutagenic and toxicpotential of the fluopyram-based pesticide, seven concentrations (0.017, 0.050, 0.210, 0.418,0.835, 1.67, and 5.00 mg mL-1) were tested in the TA100 and TA98 strains of Salmonellatyphimurium, in Artemia salina, and in seed germination and root elongation tests with lettuce(Lactuca sativa), onion (Allium cepa), and cucumber (Cucumis sativus). The results indicatethat the fluopyram-based pesticide was not mutagenic for the tested S. typhimurium strains.However, it was toxic at high concentrations, affecting A. salina survival and root elongation.The fluopyram-based pesticide applied to dystrophic red latosol soil at field concentration (1.67mg mL-1) caused short-term changes in parameters such as α-glucosidase, β-glucosidase, acidphosphatase, microbial biomass carbon (MBC), and soil metabolic quotient (qCO2). Thepesticide flumioxazin (Sumisoya®) applied in the field reduced β-glucosidase activity, affectedN-NH4+, N-NO3-, MBC, qCO2, and basal soil respiration (BSR). Of the 68 fungal strainsexposed to field concentrations of fluopyram-based pesticide (1.67 mg mL-1), flumioxazinbasedpesticide (0.25 mg mL-1), and S-metolachlor (Dual Gold® – 6.4 mg mL-1), only three strainsshowed potential tolerance: Fusarium verticillioides and Trametes versicolor. The third strainwas not identified through molecular techniques. The tolerance capacity of these speciesdemonstrates that they can be used in future experiments to evaluate the biodegradation of theassessed pesticides. Our results show that the studied pesticides cause adverse effects onnontarget organisms, impact the soil, and present fungal species with biotechnological potentialto mitigate these impacts.